Apology strategies among EFL postgraduate learners - Aboud, Farida (Cyprus International University, 2020)
This current study aimed at exploring the varieties of Apology Strategies (AS) used by EFL postgraduate learners. Besides, it investigated the relationship between AS and the gender variable. The Discourse Completion Test questionnaire (DCT) was employed as an instrument to utilize the purposes of the study. The DCT was adopted from Harb's study (2015). The respondents who participated in the study were 84 EFL learners, 42 Males (M) and 42 Females (F) respectively, who were enrolled in the master's and Ph.D. programs at Eastern Mediterranean University (EMU). The participants were from different departments and nationalities. The findings revealed that Illocutionary Force Indicating Devices (IFIDs), the accounts and reparation, were the most AS used by the respondents. Additionally, there was not a significant relationship between AS and the gender variable among EFL postgraduate learners. Based on the results, the current study provided limitations and implications for future researches. © 2019 Cyprus International University. All rights reserved.
Keywords: Apology; Apology strategies; DCT; Pragmatic competence; Speech acts